A case report of Kounis syndrome: acute myocardial injury caused by multiple bee stings - S., Megha; Agarwal, Gaurav (International Journal of Research in Medical Sciences, 2023)
Kounis syndrome, also known as “allergic angina syndrome” or “allergic myocardial infarction”, refers to acute coronary syndrome secondary to hypersensitivity reaction as a result of exposure to various allergens. Signs and symptoms may include chest pain, with or without raised troponins and cardiac enzymes, vomiting, syncope, hypotension or acute renal failure. A 60-year-old male, farmer by occupation, was bitten by multiple bees over head, neck region and bilateral upper limbs in the afternoon on 04/03/2022. On presentation, vitals were stable. After 2 hours, patient developed severe chest pain, palpitations, and dizziness. ECG showed inferior wall ST elevation MI. Subsequently CPK, CK-MB, troponin I were done, which were found to be elevated. Echocardiography was done, which showed regional wall motion abnormality in the inferior wall. Patient was treated with anticoagulants and antiplatelets. CT coronary angiography showed healthy coronaries. In literature, we had few cases of myocardial infarction following bee sting. In acute myocardial infarction after bee stings, it has been suggested that vasoconstriction secondary to mediators released after the sting, aggravated by exogenous adrenaline and platelet aggregation contributes to myocardial ischemia. Cardiac complications can accompany bee sting. Intensive supportive treatment in intensive or coronary care facilities with administration of drugs to treat complications early in the course of the illness will improve the outcome.